Learning about Capacity Development Through Evaluation. Perspectives and observations from a collaborative network of national and international organizations and donor agencies - Horton, Douglas (International Service for National Agricultural Research, 2001)
This publication is based on a Midterm Review and Synthesis Workshop for the project Evaluating Capacity Development in Research and Development Organizations, held during July 2001. This project seeks to contribute to the effectiveness of capacity development efforts in research and development organizations through the use of evaluation. The publication reviews project participants' experiences in evaluating their own capacity development efforts. It presents emerging lessons regarding capacity development and its evaluation. It then identifies major constraints to the greater use of evaluation and suggests future activities for the project and the participating organizations. For further information see the Evaluating capacity Development (ECD) website: http://www.isnar.cgiar.org/ecd/